2019
DOI: 10.1016/j.apmr.2018.08.182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Internet-Delivered Mindfulness for Improving Depression in Caregivers of People With Spinal Cord Injuries and Chronic Neuropathic Pain: A Randomized Controlled Feasibility Trial

Abstract: Objectives: To explore the feasibility and efficacy of web-based mindfulness training for carers of people with spinal cord injury (SCI). Design: Randomized controlled feasibility study with three-month follow-up. Setting: Community setting. Participants: Spouses/family caregivers of people with SCI and chronic neuropathic pain were recruited via the direct care team and advertisements. Participants were aged over 18 years (no upper age limit), with internet access for the duration of the study. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…Ultimately 90% of participants reported satisfaction with their experience. Recent studies have found virtual education can be effective in providing older adults with opportunities for exercise and improving pain management skills (19)(20)(21). Our research further supports these findings and shows that virtual programming can improve the quality of life of older adults.…”
Section: Discussionsupporting
confidence: 85%
“…Ultimately 90% of participants reported satisfaction with their experience. Recent studies have found virtual education can be effective in providing older adults with opportunities for exercise and improving pain management skills (19)(20)(21). Our research further supports these findings and shows that virtual programming can improve the quality of life of older adults.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, the different components of the support program were appreciated by the caregivers, but they expressed mixed opinions regarding the components mindfulness and peer support. Although mindfulness based interventions has been shown to decrease feelings of depression and caregiver burden in caregivers [32, 33], most caregivers in our study did not perceive the mindfulness exercises as helpful. Yet, it is not uncommon for participants to report unpleasant reactions, such as agitation, discomfort, or confusion during mindfulness interventions [34].…”
Section: Discussioncontrasting
confidence: 60%
“…With regard to the impact on anxiety, a recent meta-analysis supported the usefulness of yoga or meditation as a complementary or solo treatment of anxiety or depression [28]. It has previously been found that a 12-month yoga programs or an 8-week meditation programs can reduce anxiety and depression and diminish physical and psychological distress [15,14,29].…”
Section: Discussionmentioning
confidence: 99%